Strategi Pengembangan Usaha Produk HNI-HPAI Di Kota Timika (Studi Kasus Usaha Milik Ibu Ayu) - Ade Septian Nugraha; Zulkifka Zulkifka; Muh Sabir (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2023)
This research aims to determine Ibu Ayu's HNI-HPAI product business development strategy in Timika City. The research method used is descriptive, which is a type of research that aims to describe or describe an incident or incident. The descriptive method in this research was used to provide an overview of Mrs. Ayu's HNI-HPAI business development strategy in Timika City. In this research, the data collection techniques used were questionnaires and interviews. To find out what the business development strategy is, the analysis used in this research is a combination of Importance Performance Analysis (IPA) and Strength Weakens Opportunity Threat (SWOT). Based on the results of the Importance Performance Analysis (IPA), it shows that location accessibility and promotion are weaknesses because they have low performance, then the strengths are in service to complaints, accuracy of information related to products, thoroughness in preparing the required products, delivery of clear and fair information. in providing services. Based on the results of the SWOT analysis, the condition of the HNI-HPAI product business, Mrs. Ayu's business in Timika City is in quadrant I, which means it has good opportunities and strengths. One strategy for business development is to maintain the performance of strength attributes and make efforts to increase promotions.